2014
DOI: 10.1186/s12989-014-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of occupational exposure levels (OELs) of Low-toxicity isometric biopersistent particles: how can the kinetic lung overload paradigm be used for improved inhalation toxicity study design and OEL-derivation?

Abstract: BackgroundConvincing evidence suggests that poorly soluble low-toxicity particles (PSP) exert two unifying major modes of action (MoA), in which one appears to be deposition-related acute, whilst the other is retention-related and occurs with particle accumulation in the lung and associated persistent inflammation. Either MoA has its study- and cumulative dose-specific adverse outcome and metric. Modeling procedures were applied to better understand as to which extent protocol variables may predetermine any sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…It has also been suggested that due to the long retention times and associated bio-persistence of some materials in the lung, even short-term inhalation studies may require post-exposure periods of at least 3 months to reveal specific dispositional and toxicological characteristics. Therefore inhalation studies should be designed and executed with intermittent dosing and recovery periods to allow for the development of patterns in the accumulation and clearance at the portal of entry and manifestation of toxicity (Pauluhn, 2014). It is also important to state that the transport rate of materials, i.e.…”
Section: Summary Of the Conclusion From Inhalation Exposure Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that due to the long retention times and associated bio-persistence of some materials in the lung, even short-term inhalation studies may require post-exposure periods of at least 3 months to reveal specific dispositional and toxicological characteristics. Therefore inhalation studies should be designed and executed with intermittent dosing and recovery periods to allow for the development of patterns in the accumulation and clearance at the portal of entry and manifestation of toxicity (Pauluhn, 2014). It is also important to state that the transport rate of materials, i.e.…”
Section: Summary Of the Conclusion From Inhalation Exposure Studiesmentioning
confidence: 99%
“…In all reality, any potential pathogenic effects of inhaled NMs in the pulmonary system are dependent on a substantial lung burden which is determined by the site and extent of deposition in the lung and eventual clearance (Oakes et al 2013, Pauluhn, 2014. This deposition and clearance takes place throughout the respiratory tract and is heavily influenced by material size and surface properties (Muhlfeld et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…4) (Braakhuis et al, 2014;Pauluhn, 2011Pauluhn, , 2014. Pauluhn (2011) compared pulmonary toxicokinetics using data from rat inhalation bioassays of different types of PSPs including TiO 2 and concluded that PSP-related pulmonary toxicity was dependent on volume-based cumulative lung exposure dose.…”
Section: Approach 3: Modeling Of Precursor Lesions In Rat Lungmentioning
confidence: 98%
“…This formula involved characterizing a volume concentration of respirable particulate, which the author defined as >1 ml/lung (~6% of the alveolar macrophage volume), in which recruitment of additional phagocytic and inflammatory cells occurs. According to Pauluhn, "adversities occurring beyond this overload-threshold may follow multiple and complex cumulative-dose-dependent Adverse Outcome Pathways (AOP)" (Pauluhn, 2014). …”
Section: Evaluation Of Existing Information Characterizing Moamentioning
confidence: 98%
See 1 more Smart Citation